Beat the beam: an applied research study on sunscreen usage habits amongst young adults in Singapore - Yeo, Cassandra Jia Xi (Nanyang Technological University, 2023)
Beat The Beam is an applied communications research project aimed at addressing the fight against skin cancer through the use of sunscreen. Our project aims to develop effective strategies for promoting the usage of sunscreen as a protective measure against skin cancer in young adults aged 21 to 29 in Singapore. This project examines the efficacy of two campaign strategies: (a) message source and (b) a photoaging Augmented Reality (AR) filter in a digital health campaign.